Carotenoids: Sources, medicinal properties and their application in food and nutraceutical industry - Jaswir, Irwandi; Noviendri, Dedi; Fitri Hasrini, Reno; Octavianti, Fitri (Academic Journals, 2011)
Carotenoids are biosynthesized by bacteria, algae, fungi, and plants, but not by animals, which must obtain them from their food. These compounds are divided into two major classes based on their structural elements; carotenes, constituted by carbon and hydrogen (e.g. b-carotene, a-carotene and lycopene), and xanthophylls, constituted by carbon, hydrogen, and additionally oxygen (for example lutein, b-cryptoxanthin, zeaxanthin, astaxanthin and fucoxanthin). Carotenoids have good effect on human health, such as pro-vitamin A, antioxidant, anticancer, antiobesity effect and anabolic effect on bone components. Currently, carotenoids are used commercially as feed additives, animal feed supplements, natural food colorants, nutrient supplement and, more recently, as nutraceuticals for cosmetic and pharmaceutical purposes. These compounds can be produced commercially by chemical synthesis, fermentation or isolation from the small number of abundant natural sources. Furthermore, commercial production of carotenoids from microorganisms competes mainly with synthetic manufacture by chemical synthesis. However, most of the commercially used carotenoids (for example β-carotene, astaxanthin and cantaxanthin) are produced by chemical synthesis.